1984
DOI: 10.1126/science.224.4645.150
|View full text |Cite
|
Sign up to set email alerts
|

Helium-3 Emission Related to Volcanic Activity

Abstract: The helium-31helium4 ratio in bubbling gases from ten hot springs located around Mount Ontake, an active volcano in central Japan, ranges from 1.71 Ratm (1.71 times the atmospheric ratio of 1.40 x 10-6) to 6.15 Rat,. The value of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(42 citation statements)
references
References 2 publications
1
40
0
1
Order By: Relevance
“…5), demonstrating that the lower 3 He/ 4 He ratio is due to the addition of extraneous radiogenic helium, presumably from the surrounding host rocks. Such a subsurface crustal contamination has been observed in many instances (see Gasparon et al, 1994 and references therein) and is also responsible for the decreasing trend in the ( 3 He/ 4 He) values of volcanic gases which is classically observed away from the main conduit of volcanic edifices (Sano et al, 1984. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5), demonstrating that the lower 3 He/ 4 He ratio is due to the addition of extraneous radiogenic helium, presumably from the surrounding host rocks. Such a subsurface crustal contamination has been observed in many instances (see Gasparon et al, 1994 and references therein) and is also responsible for the decreasing trend in the ( 3 He/ 4 He) values of volcanic gases which is classically observed away from the main conduit of volcanic edifices (Sano et al, 1984. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between air-corrected 3He/4He ratio and distance of the sampling location from the central cone Kamiyama (Fig. 3(b)) indicates that (1) 3He/4He ratios of samples within the caldera of Hakone volcano are high and uniform, (2) magmatic components in the Yufune and Nakagawa samples are assumed to have been derived from the Hakone volcano, because there is no other near-by Quaternary Figure 4 compares the air-corrected 3He/4He distribution and least-squares fit for the Hakone volcano with those of other volcanoes, such as Ontake volcano, Japan (Sano et al, 1984), Nevado del Ruiz volcano, Columbia (Williams et al, 1987;Sano et al, 1990), and Kusatsu Shirane volcano, Japan (Marty et al, 1989). There is a general trend of 3He/4He ratio decreas ing with distance from the main cone of each volcano.…”
Section: Resultsmentioning
confidence: 99%
“…Distinct S wave reflectors at shallower depths of 10-18 km in or around the low-velocity zones observed in various volcanic regions in Japan are inferred to correspond to the upper surface of magma bodies. Geochemical investigation based on the (Sano et al, 1984), Nevado del Ruiz (Williams et al, 1987;Sano et al, 1990) and Kusatsu-Shirane (Marty et al, 1989). Distance from the main cone (km) of 3He/4He ratio distribution helium isotope measurement may provide vital information of the distribution and movements of magma bodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a decreasing trend of helium isotopes was found with increasing distance from the central cone to the sampling sites (Sano et al, 1984). Such a tendency may be characteristic of 3 He emission in volcanic areas and suggested that magmatic helium was carried with fluid-flowing through a conduit.…”
Section: Introductionmentioning
confidence: 93%